Baseline modified Glasgow Prognostic Score (mGPS) predicts radiologic response and overall survival in metastatic hormone-sensitive prostate cancer treated with docetaxel chemotherapy - Neuberger, Manuel; Skladny, Janina; Goly, Nora; Wessels, Frederik; Weiß, Christel; Egen, Luisa; Erben, Philipp; Groß-Weege, Matthias; Grüne, Britta; Hartung, Friedrich; Herrmann, Jonas; Honeck, Patrick; et al. (Anticancer research, 2022)
Background/Aim: To assess the baseline inflammatory markers modified Glasgow Prognostic Score (mGPS), systemic immune-inflammation index (SII), and neutrophile-to-lymphocyte ratio (NLR) as pragmatic tools for predicting response to chemohormonal therapy (docetaxel plus ADT) and prognosis in men with metastatic hormone-sensitive prostate cancer (mHSPC). Patients and Methods: Male patients who received docetaxel at a tertiary university care center between 2014 and 2019 were screened for completion of 6 cycles. NLR, SII, mGPS, overall survival (OS), three-year survival, and radiologic response were assessed. Complete response (CR), partial response (PR), and stable disease (SD) were analyzed alone and in combination. Results: Thirty-six mHSPC-patients were included. In thirty patients, baseline mGPS was assessed and was either 0 (n=22) or 2 (n=8). In Cochran-Armitage Trend Test, mGPS showed significant association with the combined radiologic endpoint of “CR, PR, or SD” (p=0.01), three-year survival (p=0.02), and OS (p<0.01). Next to prostate-specific antigen (PSA) (HR per 100 units 1.16, 95%CI=1.04-1.30, p<0.01), NLR (HR=1.31, 95%CI=1.03-1.66, p=0.03), and mGPS (2 vs. 0, HR=6.53, 95%CI=1.6-27.0, p<0.01) at baseline showed significant association with OS in univariable cox regression. However, mGPS remained the only independent predictor for OS in multivariable cox regression (p<0.01) and for the combined radiologic endpoint of “CR, PR or SD” (p=0.01) in multivariable logistic regression. SII showed no statistical relevance. Conclusion: Baseline mGPS seems to be a pragmatic tool for clinical decision-making in patients with mHSPC in daily routine.
Online veröffentlicht: 28. März 2022
Margarete Teresa Walach ist fälschlich als Margarete Theresa Walach geschrieben
Gesehen am 25.03.2024